Genetic Diversity and Geographic Distribution of Cucurbit-Infecting Begomoviruses in the Philippines - Zhuan Yi Neoh; Hsuan-Chun Lai; Chung-Cheng Lin; Patcharaporn Suwor; W. S. Tsai (Plants, 2023)
(SLCuPV) are associated with CuLCD. SLCuPV and SLCCNV were identified in Luzon, the Philippines. Here, the genetic diversity and geographic distribution of CuLCD-associated begomoviruses in the Philippines were studied based on 103 begomovirus detected out of 249 cucurbit samples collected from 60 locations throughout the country in 2018 and 2019. The presence of SLCCNV and SLCuPV throughout the Philippines were confirmed by begomovirus PCR detection and viral DNA sequence analysis. SLCuPV was determined as a predominant CuLCD-associated begomovirus and grouped into two strains. Interestingly, SLCCNV was detected in pumpkin and bottle gourd without associated viral DNA-B and mixed-infected with SLCuPV. Furthermore, the pathogenicity of selected isolates of SLCCNV and SLCuPV was confirmed. The results provide virus genetic diversity associated with CuLCD for further disease management, especially in developing the disease-resistant cultivars in the Philippines as well as Southeast Asia.
Keywords: Plant Virus Research Studies; Plant Disease Management Techniques; Plant and Fungal Interactions Research